From Akhenaten to Moses : ancient Egypt and religious change - Assmann, Jan. (Cairo ; New York : American University In Cairo Press, 2014)
The shift from polytheism to monotheism changed the world radically. Akhenaten and Moses-a figure of history and a figure of tradition-symbolize this shift in its incipient, revolutionary stages and represent two civilizations that were brought into the closest connection as early as the Book of Exodus, where Egypt stands for the old world to be rejected and abandoned in order to enter the new one. The seven chapters of this seminal study shed light on the great transformation from different angles. Between Egypt in the first chapter and monotheism in the last, five chapters deal in various ways with the transition from one to the other, analyzing the Exodus myth, understanding the shift in terms of evolution and revolution, confronting Akhenaten and Moses in a new way, discussing Karl Jaspers' theory of the Axial Age, and dealing with the eighteenth-century view of the Egyptian mysteries as a cultural model. --publisher's description.
Structure and Change in Ancient Egyptian Religion -- Myth and History of the Exodus: Triumph and Trauma -- From Polytheism to Monotheism: Evolution or Revolution? -- Moses and Akhenaten: Memory and History -- Ancient Egypt and the Theory of the Axial Age -- Egyptian Mysteries and Secret Societies in the Age of Enlightenment -- Total Religion: Politics, Monotheism, and Violence.
Includes bibliographical references and index.
Keywords: Moses -- (Biblical leader); Akhenaton, -- King of Egypt; Egypt -- Religion; Egypt -- Kings and rulers; Egypt -- History -- Eighteenth dynasty, ca. 1570-1320 B.C.